Pengaruh Content Marketing, Influencer Marketing dan Personalisasi Iklan Terhadap Keputusan Pembelian Pada Tiktok Shop (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang) - Ulfa, Mariana; Wahono, Budi; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Goals of the research is to analyzing and testing the affect of content marketing, influencer marketing, and advertising personalization on purchasing decisions on the TikTok Shop platform. Using a quantitative approaches, that have the population within 688 respondents, used the Malhotra formula. In this study, using fixed 100 respondents. Analyzing data used multiple linear regression, t test, and f test, also SPSS software to help the test the research hypothesis. The results show that content marketing, influencer marketing, and advertising personalization affecting the purchasing decisions on TikTok Shop significantly, with both partial and simultaneous. Keywords: Content Marketing, Influencer Marketing, Advertising, Personalization, Purchasing Decisions